"JANETTI" JASA INTERNET MARKETING GUNA MENUNJANG USAHA MIKRO KECIL MENENGAH DALAM MENGHADAPI PERSAINGAN PASAR DI ERA EKONOMI DIGITAL DI DESA KALORAN BRIMOB KAB. SERANG. - Yubaedah, Ida Yubaedah; Susanto, Denies; Musfiroh, Fifi (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Kaloran Brimob Village, Serang Regency, face significant challenges in market competition in the digital economy era due to limited internet marketing literacy and implementation. The purpose of this community service program is to provide training and mentoring in the implementation of JANETTI (Internet Marketing Services) as a strategic solution to increase MSME competitiveness. Implementation methods include needs assessment, outreach, intensive training (utilization of social media, e-commerce, and Google Business), as well as practical mentoring and sustainability evaluation. The results show a significant increase in understanding of digital marketing, the establishment of digital business accounts, and an increase in the promotional reach of local MSME products. Qualitatively, partner MSMEs have become more confident in facing digital market competition. The JANETTI program has proven effective as a catalyst for digital transformation for MSMEs in Kaloran Brimob Village.